Fundamentals of thermal-fluid sciences - Cengel, Yunus A.; Cimbala, John M.; Turner, Robert H. (McGraw Hill, 2012)
Designed for the non-mechanical engineering student who needs exposure to key concepts in the thermal sciences in order to pass the Fundamentals of Engineering (FE) Exam, this title features a return of Power and Refrigeration Cycles coverage in a fresh chapter as well as more examples featuring sustainability and green technology